Determinants of territorial differences in entrepreneurial rates. An empirical analysis of Italian local systems - Giulio Cainelli; Donato Iacobucci; Alessandra Micozzi (European Regional Science Association (ERSA), 2013)
According to the last GEM (Global Entrepreneurship Monitor) surveys, Italy has one of the lowest rates of entrepreneurial activity among innovation driven countries. Moreover, Italy is characterized by large territorial differences in the entrepreneurial rates. The main aims of this paper are to provide a better understanding of the factors affecting territorial differences in entrepreneurial rates and to explain their persistence over time. Specifically, the paper compares the relative importance of socio-demographics factors, such as activity rates and social capital, and economic factors, such as the structure and organization of local production systems. The persistence of territorial differences may depend on the persistence of differences in explanatory variables or on the path dependent effect. For the empirical analysis, we consider the creation of new firms in Italy from 2001 to 2009 using the Movimprese database provided by the Chambers of Commerce. The database provides information on new firm formation at territorial level (103 provinces) and disaggregated by sector of activity. Using the adult population as normalizing variable, the entrepreneurial rate is defined as the total number of new firms in a year on the adult population at the beginning of the year. We consider entrepreneurial rates referring to the overall sectors and for the manufacturing industry. For the econometric estimates we use several sets of independent variables, referring to push and pull factors. Some of the variables refer to structural characteristics and for this reason are time-invariant (this is the case of the social capital index). Other variables vary by province and by year. The first result is that the territorial differences of entrepreneurial rates shows a strong persistence over time: provinces with high entry-rates in the past are most likely to have high level of start-up activity in the future. This is true most of all for the new firms in manufacturing sectors where the factors linked to the social and economic context are important are stable over time. Moreover, socio-demographic factors show a higher relevance in explaining territorial differences in entrepreneurial rates than economic factors. This is valid for the total entrepreneurial rate as well as for explaining new firm formation in manufacturing sectors.
Keywords: 330; firm birth; entrepreneurial rates; path dependence; local production systems